2017
DOI: 10.1037/dev0000218
|View full text |Cite
|
Sign up to set email alerts
|

Children’s daily well-being: The role of mothers’, teachers’, and siblings’ autonomy support and psychological control.

Abstract: This study examined the unique relations between multiple sources (i.e., mothers, teachers, and siblings) of perceived daily autonomy support and psychological control and children's basic psychological needs and well-being. During 5 consecutive days, 2 children from 154 families (Mage youngest child = 8.54 years; SD = .89 and Mage oldest child = 10.38 years; SD = .87) provided daily ratings of the study variables. Multilevel analyses showed that each of the sources of perceived autonomy support and psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
155
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 177 publications
(201 citation statements)
references
References 81 publications
(121 reference statements)
18
155
1
2
Order By: Relevance
“…In one of the few previous studies addressing between-day associations between parenting and child outcomes, Aunola et al (2013) found that children's negative emotions during a given day predicted decreases (rather than increases) in psychological control the next day. This negative betweenday association differs from the positive associations between children's negative emotions and parental psychological control typically obtained at the level of betweenperson differences (Barber, 1996; and at the level of within-day associations (Van der Kaap-Deeder, Soenens, et al, n.d.;Van der Kaap-Deeder, Vansteenkiste, et al, 2017). Future research on daily dynamics of parenting would do well to more systematically estimate and compare within-day and between-day associations.…”
Section: Direction Of Effects In Associations Between Parental Psychomentioning
confidence: 75%
See 3 more Smart Citations
“…In one of the few previous studies addressing between-day associations between parenting and child outcomes, Aunola et al (2013) found that children's negative emotions during a given day predicted decreases (rather than increases) in psychological control the next day. This negative betweenday association differs from the positive associations between children's negative emotions and parental psychological control typically obtained at the level of betweenperson differences (Barber, 1996; and at the level of within-day associations (Van der Kaap-Deeder, Soenens, et al, n.d.;Van der Kaap-Deeder, Vansteenkiste, et al, 2017). Future research on daily dynamics of parenting would do well to more systematically estimate and compare within-day and between-day associations.…”
Section: Direction Of Effects In Associations Between Parental Psychomentioning
confidence: 75%
“…Research convincingly demonstrated associations between psychologically controlling parenting and children's and adolescents' ill‐being and behavioural maladjustment (Barber & Xia, ; Soenens & Vansteenkiste, ). Recent studies began to show that such effects also occur on a day‐to‐day basis, with daily psychologically controlling parenting being related to daily maladjustment in children (Aunola et al, ; Van der Kaap‐Deeder, Vansteenkiste, et al, ). This study aimed to contribute to this emerging literature (i) by revisiting associations between daily parental psychological control and children's daily maladjustment using a multi‐informant approach and, most importantly, (ii) by investigating the role of children's personality at the level of within‐person variation in daily psychologically controlling parenting in the prediction of child outcomes, and (iii) by examining lagged associations between daily parental psychological control and child outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is important because mediation refers to dynamic processes that change across time (Selig & Preacher, 2009). Particularly in adolescence, personality (Klimstra, 2013), needbased experiences (Van der Kaap-Deeder, Vansteenkiste, Soenens, & Mabbe, 2017), and symptoms of psychopathology (Larson, Moneta, Richards, & Wilson, 2002) are highly susceptible to change. This raises the question of whether need frustration plays a role at (a) the between-person level (i.e., accounting for between-person differences in self-critical perfectionism and symptoms,) and (b) the within-person level (i.e., accounting for associations between intra-individual change in self-criticism and intra-individual change in symptoms).…”
Section: The Present Studymentioning
confidence: 99%